The Effect Of The Multisensory Method On The Beginning Reading Ability Of Children In Group B Kb Thia Ananda Mariana - Hilmawati Hilmawati; Darwin Effendi; Padilah Padilah (Journal on Education, 2024)
This study aims to determine the effect of the Multisensory Method on the Beginning Reading Ability of Group B Children in the Thia Ananda KB Year 2023, Banyuasin Regency. This study uses an experimental method with the type of One-Group Pretest-Posttest Design. That this type of method has a pretest before being given treatment (treatment). The population in this study were 26 children and 16 children in group B were taken as a sample. The method used to collect research data was through observation, interviews, and oral tests. The research data were analyzed using the SPSS 26 26 for Windows program with a significant level of 0.05. From the results of the analysis and discussion, sig = 0.000 <0.05 with a tcount value of -28.114 > 1.753. It can be concluded that Ho is rejected and Ha is accepted. There is a significant effect on the early reading ability of group B children in the Thia Ananda Mariana KB.